Comparative analysis of internal limiting membrane peeling versus internal limiting membrane flap insertion for treating idiopathic macular holes - Xueying Ma; Jie Sun; Qiaohong Liang; Yuerong Kong; Hong Yang; Xiaogang Huang (Photodiagnosis and Photodynamic Therapy, 2024)
Objective: To evaluate the clinical efficacy of internal limiting membrane (ILM) peeling combined with perimacular hole massage versus ILM flap insertion in the management of patients with idiopathic macular holes was conducted. Methods: 35 patients (total of 35 eyes) with idiopathic macular holes (with hole diameters ranging from 366 to 1430 μm) were divided into two groups—Group A consisted of 20 eyes that underwent pars plana vitrectomy (PPV) combined with ILM peeling and perimacular hole massage, while Group B comprised 15 eyes that underwent PPV combined with ILM flap insertion. Subsequent follow-up examinations were performed at 1 week, 1 month, and 3 months post-surgery. The study also involved a comparison of best corrected visual acuity (BCVA) and optical coherence tomography (OCT) classifications between both the patient groups. Results: The macular hole closure rates in Group A were 60 %, while in Group B, the closure rate was 93 %. There was significant difference in hiatus healing rate between the two groups (t = 4.843, p = 0.048). The difference in BCVA at 3 months post-operation between the two groups was statistically significant (t = 3.221, p = 0.003). Three months post-operatively, the BCVA in Group B demonstrated improvement compared to the pre-operative BCVA, with a statistically significant difference (p > 0.05). Three months post-operatively, the BCVA in Group A demonstrated improvement compared to the pre-operative BCVA, but this difference was not statistically significant (p > 0.05). Conclusion: The combination of PPV with ILM flap insertion demonstrates favorable therapeutic efficacy in the treatment of idiopathic macular holes, leading to improved visual acuity.